Comparative proteomes, immunoreactivities and neutralization of procoagulant activities of Calloselasma rhodostoma (Malayan pit viper) venoms from four regions in Southeast Asia. (November 2019) - Tang, Esther Lai Har; Tan, Nget Hong; Fung, Shin Yee; Tan, Choo Hock
Abstract: The intraspecific geographical venom variations of Calloselasma rhodostoma from Malaysia (CR-M), Indonesia (CR-I), Thailand (CR-T) and Vietnam (CR-V) were investigated through 1D SDS-PAGE and nano-ESI-LCMS/MS. The venom antigenicity, procoagulant activities and neutralization using Thai C. rhodostoma Monovalent Antivenom (CRMAV) were also investigated. SDS-PAGE patterns of the venoms were relatively similar with minor variations. Proteomic analysis revealed that snake venom metalloproteinases (SVMPs, particularly P–I class), serine proteases (SVSPs) and snaclecs dominated the venom protein composition (68.96–81.80%), followed by L-amino acid oxidase (LAAO) and phospholipase A2 (PLA2 ) (7.37–11.08% and 5.18–13.81%, respectively), corroborating C. rhodostoma envenoming effects (hemorrhage, consumptive coagulopathy, thrombocytopenia and local tissue necrosis). Other proteins of lower abundances (2.82–9.13%) identified include cysteine-rich secretory proteins (CRISP), phospholipase B, phosphodiesterase, nerve growth factor, 5′-nucleotidase, aminopeptidase and hyaluronidase. All four venoms exhibited strong procoagulant effects which were neutralized by CRMAV to different extents. CRMAV immunoreactivity was high toward venoms of CR-M, CR-I and CR-T but relatively low for CR-V venom. Among the venom samples from different locales, CR-V venom proteome has the smallest SVMP composition while SVSP, PLA2 and phosphodiesterase were more abundant in the venom. These variations in C. rhodostoma venom protein composition could partly explain the differences seen in immunoreactivity. (198 words). Graphical abstract: Image 1 Highlights: Geographical variations of Calloselasma rhodostoma venom were investigated. Specimens were from Malaysia, Indonesia, Thailand and Vietnam. Major protein families were commonly present among the different venoms. Procoagulant effects of all venoms were neutralized by CRMAV to different extents. CRMAV immunoreactivity was relatively lower toward the venom from Vietnam.